If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(5x + -2) = 4(2x + -3) Reorder the terms: -4(-2 + 5x) = 4(2x + -3) (-2 * -4 + 5x * -4) = 4(2x + -3) (8 + -20x) = 4(2x + -3) Reorder the terms: 8 + -20x = 4(-3 + 2x) 8 + -20x = (-3 * 4 + 2x * 4) 8 + -20x = (-12 + 8x) Solving 8 + -20x = -12 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 8 + -20x + -8x = -12 + 8x + -8x Combine like terms: -20x + -8x = -28x 8 + -28x = -12 + 8x + -8x Combine like terms: 8x + -8x = 0 8 + -28x = -12 + 0 8 + -28x = -12 Add '-8' to each side of the equation. 8 + -8 + -28x = -12 + -8 Combine like terms: 8 + -8 = 0 0 + -28x = -12 + -8 -28x = -12 + -8 Combine like terms: -12 + -8 = -20 -28x = -20 Divide each side by '-28'. x = 0.7142857143 Simplifying x = 0.7142857143
| x=9x+40 | | -6d-3d+3=-12 | | 20x^3-40x=0 | | 7x-21y=-14 | | 6l+4m-5l-4m-l+m= | | 3(4x-7)=-2(3x-5) | | 3X-4(X-2)=7+5(X+5) | | 3a=6(a-3) | | 5/3x18 | | 2(3x+8)=5(x+2) | | 20x^2-x-4=0 | | 15n^3+20n^2= | | 9x-2=x+6 | | x*55=-220 | | 27x^2+36x-6x-8= | | x/2=7/11 | | f(6)=.03x^2+.06x+31.4 | | 6n-3n*2n+n= | | (x-(-2i))(x+(-2i))=0 | | x/6=9/11 | | x^-2y^2/x^4y^-3 | | 4x+2y-3x-5y= | | 3a+2=4a+2 | | y+2=.8(x+4) | | (x^2)*logx=k | | q^2/q | | 3x-2=2x+15 | | 5u+1=8 | | 8(8-1)=4 | | 42=3z | | p*q=(100-8q)q | | 30/12= |